Menimbang Gagasan Bryan S. Turner tentang Islam - Turmudi, Imam (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This article explores the study of Islam by an orientalist, Bryan S. Turner. This study aimed to: first, to uncover the things that underlie the history of thought and movement of Orientalism. Second, to determine the thought Bryan S. Turner about Islam, which is specifically intended as a corrective to the thesis produced by Max Weber about his interpretation of Islam. The results of the study reveal that historically Orientalism, or the oriental studies movement emerged in the 18th century. This movement is often associated as a movement that pretend to control and weaken the East, especially Islam. It is not without basis, since the emergence of Orientalism has led to intellectual arrogance by claiming the West as a measure of civilization, because the East presented only in accordance with the construction used by the West. Keywords: Orientalism, Orient, West, civilization.